2017
DOI: 10.1177/1971400917712530
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular pseudodiverticula from intraparenchymal cerebrospinal fluid dissection secondary to high-grade obstructive hydrocephalus in children: magnetic resonance imaging findings

Abstract: We report on a series of three children who presented with a focal cerebrospinal fluid collection within the periventricular white matter of the temporal and occipital lobes in the setting of high-grade obstructive hydrocephalus. Magnetic resonance imaging showed a focal defect within the ventricular wall associated with leakage of cerebrospinal fluid into the adjacent white matter. The white matter tracts appeared primarily displaced. This entity should be referred to as ventricular pseudodiverticulum, not li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…These findings suggest that epigenetic mutations may indirectly affect the development and function of ependymal cells by disrupting the overall regulation of gene expression. Alternatively, the MRI findings described in our patient may be explained by pseudodiverticula formation caused by ventricular wall defects and the absence of ependymal cell lining from long‐standing hydrocephalus 26 . Such pseudodiverticula may resemble porencephalic cysts associated with ischemic lesions and extensive white matter gliosis.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…These findings suggest that epigenetic mutations may indirectly affect the development and function of ependymal cells by disrupting the overall regulation of gene expression. Alternatively, the MRI findings described in our patient may be explained by pseudodiverticula formation caused by ventricular wall defects and the absence of ependymal cell lining from long‐standing hydrocephalus 26 . Such pseudodiverticula may resemble porencephalic cysts associated with ischemic lesions and extensive white matter gliosis.…”
Section: Discussionmentioning
confidence: 67%
“…Such pseudodiverticula may resemble porencephalic cysts associated with ischemic lesions and extensive white matter gliosis. The two entities may be differentiated by diffusion tensor imaging that can assess the integrity of periventricular white matter tracts, which should be largely intact around pseudodiverticula but disrupted around porencephalic cysts 26 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They may also occur along the suprapineal and infrapineal recesses of the third ventricle and the superior portion of the fourth ventricle. [ 4 5 ] A recent study suggested that the presence of ventricular diverticula at the level of the temporal horn might also be explained by the less compact packing of the subependymal white matter bundles in this region. [ 3 ] The diffuse tensor imaging (DTI) study of a patient who presented with hemiparesis consistent with the intraparenchymal lesion revealed that the corticospinal tract was partly included in the septum between the ventricle and the intraparenchymal diverticulum.…”
mentioning
confidence: 99%